PERANGKAT AJAR MATERI VEGETATIF BUATAN PADA TUMBUHAN DI SMA NEGERI 9 KOTA BENGKULU MENGGUNAKAN 3DS MAX - Kanedi, Indra; Zulita, Leni Natalia (Jurnal Media Infotama, 2011)
Device teaching on artificial vegetative plant material in SMAN 9 Bengkulu city using 3ds Max. The place and time of the research conducted in the city of Bengkulu SMA N 9th Street Sharks WR Supratman monument city of Bengkulu, the methods used in this research system development methods, and methods of data collection by means of literature study, observation and interviews. The research program aims to make the teaching of artificial vegetative materials in plants in SMAN 9 Bengkulu city using 3ds Max, which contains some animation and sound. The results of the discussion in this research is the achievement of the instructional program vagaetatif artificial materials in plants in SMAN 9 Bengkulu city is expected to enhance the teaching and learning process better. Keywords: 3ds Max, hardwares of teaching, artificial vegetative